Two opportunities to deliver on the Doha Development pledge - Bouët, Antoine; Mevel, Simon; Orden, David (International Food Policy Research Institute, 2006)
In this brief, we evaluate the effects of a possible Doha agreement based on proposals currently on the table from the United States, the European Union, and the Group of Twenty (G20)....[The brief presents] two development-oriented alternatives...which demonstrate that more can be accomplished in the Doha Round if these two development-oriented and pro-trade measures are used.